Experimental and simulation research on heat extraction characteristics from a pilot-scale reverse flow reactor for low-grade energy. (5th February 2023) - Zhou, Yuqi; Shi, Yueyue; Liu, Yongqi; Sun, Peng; Mao, Mingming
Highlights: The thermal flow reversal reactor with heat recovery systems is constructed. Low flowrate contributes to establishing initial temperature field. Steam with 148 kg and 511 K can be produced at 1 % concentration. The optimum reversing time in this paper is 120 s. The link between temperature evolution and heat extraction is preliminary explored. Abstract: This work presents heat extraction characteristics in a pilot-scale thermal flow reversal reactor dedicated to the mitigation of ventilation air methane escaping from coal mining and the recovery of residual heat. The heat extraction mode arranged on both sides of the central zone was applied. The influence of flowrate, concentration and reversing time on comprehensive heat transfer performance were investigated through experiments. The temperature evolutions and the quantitative relationship between temperature evolutions and heat extraction were predicted through simulations. The experimental results show that low flowrate is susceptible to establishing rapidly initial temperature field. The heat recovery rate and generated superheated steam increase with concentration and varies parabolically with switch time. The optimum heat extraction is that heat recovered is slightly greater than or close to the stored heat. Therefore, the heat extraction research involved in this paper will provide a reference for other low-grade waste fuels in industrial applications.